The Role of Brand Image on Repurchase Intention of Le Minerale Mediated by Brand Equity in Semarang - Mukminah; Imam Nuryanto (MultiTech Publisher, 2024)
This study aims to analyze the influence of brand image on repurchase intention of Le Minerale products in Semarang, emphasizing the role of brand equity as a mediator. Using quantitative analysis methods and Smart PLS, the results of the study show that brand image has a positive and significant influence on repurchase intentions. In addition, brand equity was shown to serve as a significant mediator in the relationship between brand image and repurchase intention. These findings confirm that strengthening brand image not only directly affects repurchase intentions but also through increasing brand equity. This research provides important insights for companies in formulating effective marketing strategies to increase product repurchase intentions.